CYP3A4 intronic SNP rs35599367 (CYP3A4*22) alters RNA splicing - Wang, Danxin (Pharmacogenet Genomics, 2016)
Cytochrome P450 3A4 (CYP3A4) metabolizes 30–50% of clinically used drugs. Large interperson variability in CYP3A4 activity affects response to CYP3A4 substrate drugs. We had demonstrated that an intronic single nucleotide polymorphism (SNP) rs35599367 (CYP3A4*22, located in intron 6) reduces mRNA/protein expression; however, the underlying mechanism remained unknown. Here we show that CYP3A4*22 is associated with a twofold or greater increase in formation of a nonfunctional CYP3A4 alternative splice variant (aSV) with partial intron 6 retention in human liver (p=0.006), but not in small intestines. Consistent with this observation, in vitro transfection experiments with a CYP3A4 minigene (spanning from intron 5 to intron 7) demonstrated that plasmids carrying the rs35599367 minor T allele caused significantly greater intron 6 retention than the C allele in liver derived HepG2 cells, but not in intestine-derived LS-174T cells. These results indicate that tissue specific increased formation of nonfunctional aSV causes reduced CYP3A4 mRNA/protein expression in CYP3A4*22 carriers.